Study on seed quality testing of Russian dandelion - G. Shen; L. Zhou; F. Zheng; Zh. Yu; Y. Yang; W. Zhang; N. G. Kon’kova (Труды по прикладной ботанике, генетике и селекции, 2025)
Background. Kok-saghyz, or Russian dandelion, is one of the three most promising natural rubber plants in the world. This study examined the seed quality of kok-saghyz from different sources with reference to the methods in the International Rules for Seed Testing.Materials and methods. A kok-saghyz accession from the VIR collection (k-445) and an accession of American origin were analyzed. The study was carried out in 2018–2020 under the conditions of a field experiment at the experiment station in Harbin (45.592729°N, 126.581668°E).Results. Sampling principles and methods were established, and the seed quality of kok-saghyz was thoroughly evaluated. A seed purity test showed above 80% of pure seeds for both accessions. The thousand-seed weight was approximately 0.5 g when measured by the hundred-seed method. The moisture content was about 5.4% according to the low-temperature drying technique. The time required for reaching a natural imbibition rate was 2.5 h. The authenticity test demonstrated that koksaghyz seeds can be distinguished from those of other Taraxacum spp. according to their appearance. The health test found 4 types of mold inside and outside the kok-saghyz seeds.Conclusion. This study provides technical support for kok-saghyz seed quality testing, and offers recommendations for koksaghyz seed trade.